The Adaptation of Assistive Technology in Inclusive Education: an Analysis of Recent Trends in Teaching English - Hanifah, Aliyya; Subroto, Ibnu; Ramadhan, Arrizqi (Jurnal Multidisiplin Sahombu, 2025)
This study explores the adaptation of assistive technology (AT) in inclusive education, particularly in the context of teaching English as a Foreign Language (EFL). It aims to examine how assistive tools are implemented in inclusive schools, the challenges experienced by educators, and the extent to which such technologies influence student learning outcomes. The research was conducted at SLB Negeri 08 Jakarta and SLB Negeri 11 Jakarta. A qualitative descriptive method was employed, utilizing interviews and documentation as the primary data collection techniques. Data analysis was supported by Natural Language Processing (NLP) tools to identify recurring patterns and thematic categories. The findings reveal that assistive technology plays a crucial role in facilitating communication, enhancing comprehension, and improving accessibility for students with special needs. SLB Negeri 08 predominantly used simple visual aids for learners with intellectual disabilities, whereas SLB Negeri 11 integrated digital tools such as Chromebooks and LCD projectors to support students with hearing impairments. Despite its benefits, several challenges were identified, including limited infrastructure, insufficient teacher training, and varying levels of digital literacy among educators. Nevertheless, the use of assistive technology significantly increases student engagement, builds confidence, and strengthens inclusive participation within the classroom. Overall, this study highlights that assistive technology functions not only as an instructional aid but also as a transformative mechanism that helps bridge educational gaps and promotes equity in inclusive learning environments.